Bedouin tribes of the Euphrates - Blunt, Anne, Lady, 1837-1917 (My University, 1879)
The book provides some historical information about the peoples living in Asia, including the Armenians
By Lady Anne Blunt.- Edited with a preface and some account of the Arabs and their horses, by W.S.B. Map and sketches by the author. - New York, Harper & Brothers, 1879.- 445 p. front., plates, fold. map, fold. tab.- 23 cm.
Գիրքը ՀԱԳ- ում բացակայում է։ Տվյալները՝ ԱՄՆ-ի Կոնգրեսի գրադարանից
https://www.loc.gov/item/15023689/
Keywords: Horses-Breeding-Arabian Peninsula; Euphrates River Valley